Correlation between serum levels of proprotein convertase subtilisin/kexin type 9 (PCSK9) and atherogenic lipoproteins in patients with coronary artery disease. Issue 1 (December 2016) - Nozue, Tsuyoshi; Hattori, Hiroaki; Ogawa, Kazuyuki; Kujiraoka, Takeshi; Iwasaki, Tadao; Hirano, Tsutomu; Michishita, Ichiro
Abstract Background Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a key regulator of serum low-density lipoprotein (LDL) cholesterol levels. Recently, PCSK9 has additionally been related to metabolic risk factors such as the levels of triglycerides, apolipoprotein B (apoB), insulin, and glucose, as well as body mass index. The purpose of this study was to investigate correlations between serum levels of PCSK9 and apoB-containing atherogenic lipoproteins in patients with coronary artery disease (CAD). Methods Serum levels of PCSK9 and lipoprotein(a) [Lp(a)]; small, dense LDL; and oxidized LDL were measured in 101 patients with CAD who were not receiving lipid-lowering therapy. Results Serum hetero-dimer PCSK9 levels were positively correlated with serum levels of Lp(a) (r  = 0.195, p  = 0.05); small, dense LDL (r  = 0.336, p  = 0.0006); and oxidized LDL (r  = 0.268, p  = 0.008). Multivariate regression analyses showed that serum hetero-dimer PCSK9 was a significant predictor of serum levels of Lp(a) (β  = 0.235, p  = 0.01); small, dense LDL (β  = 0.143, p  = 0.03); and oxidized LDL (β  = 0.268, p  = 0.008). Conclusions Serum PCSK9 levels were positively correlated with serum levels of Lp(a); small, dense LDL; and oxidized LDL in patients with CAD. This suggests that the interaction between serum PCSK9 and apoB-containing lipoproteins plays a role in establishing the atherosclerotic status of patients. Trial registration UMIN Clinical Trials Registry, UMIN ID:C000000311 .